Tinjauan Kasus-kasus Konsolidasi Laporan Keuangan: Analisis terhadap Perbedaan Perlakuan Akuntansi antara PSAK dan IFRS - Masrukhan, Masrukhan; Sari, Novyta; Zulfah, Erin Khairin (PENG: Jurnal Ekonomi dan Manajemen, 2025)
The purpose of this study is to examine the differences in accounting practices between International Financial Reporting Standards (IFRS) and Financial Accounting Standards Statements (FSAs) in the consolidation of financial statements. The main objective of this study is to analyze various aspects of different accounting standards and identify the implications of these differences in the analysis of financial data. This study examines critical areas such as the recognition, measurement, presentation, and elimination of assets and liabilities through case studies of several companies that use PSAK and IFRS standards. The findings of the study show that these differences in the accounting process have an impact on the consistency, transparency, and comparability of financial statements across entities. It is hoped that this will help practitioners and regulators understand and reduce differences in financial reporting and promote international accounting standardization.